Investigate Bending Effect of Wearable GPS Patch Antenna with Denim and Polyester Fabric Substrate - Kavinesh S Radhakrishna; M.S. Shakhirul; Y.S. Lee; K.N. Khairina; A.R.A Syafiqah (International Journal of Electronics and Telecommunications, 2023)
In high technologies today, wearable devices have become popular. Wearable technology is a body sensing system that supports application of health observance and tracking through a wearable Global Positioning System (GPS). The design of the patch antennas is highly significant for the brilliance of the wearable patch antennas. This paper focuses on analyzing the bending effect on return loss and frequency between three types of GPS patch antenna. Types of GPS patch antennas that have been designed in this project are with different substrates and different designs. The wearable patch antenna has been designed and analyse using CST software. As a result, able to analysis the reflection coefficient (S11), radiation patterns, and analytical approach for patch antenna bending effect were obtained.